Effect of benzylpenicillin on intravenous pharmacokinetics of acyclovir in red‐eared slider turtles (Trachemys scripta elegans) - D. Corum, Duygu; Corum, Orhan; Atik, Orkun; E. Faki, Hatice; Altan, Feray; Uney, Kamil (Wiley, 2020)
AbstractThe aim of this study was to determine the effect of benzylpenicillin on the pharmacokinetics of acyclovir in red‐eared slider turtles (Trachemys scripta elegans). Six clinically healthy red‐eared slider turtles weighing 400 and 580 g were used for the study. Acyclovir (40 mg/kg) and benzylpenicillin (30 mg/kg) were administered intravenously to turtles. In the study, the cross‐pharmacokinetic design (2 × 2) with a 30‐day washout period was performed in two periods. Plasma concentrations of acyclovir were assayed using the high‐performance liquid chromatography with fluorescence detection. Pharmacokinetic parameters were calculated by two‐compartment open pharmacokinetic model. Following the administration of acyclovir alone, elimination half‐life (t1/2β), area under the plasma concentration–time curve (AUC), total clearance (ClT), and volume of distribution at steady‐state (Vdss) were 20.12 hr, 1,372 hr * µg/mL, 0.03 L hr−1 kg−1, and 0.84 L/kg, respectively. Benzylpenicillin administration increased t1/2β, AUC, and Vdss while decreased ClT of acyclovir. These results showed that benzylpenicillin changed the pharmacokinetics of acyclovir following simultaneous administration in turtles. However, further research is needed to determine molecular mechanism of interaction in turtle.
Keywords: Cross-Over Studies; Acyclovir; Penicillin G; Benzylpenicillin; Antiviral Agents; Anti-Bacterial Agents; Turtles; Area Under Curve; Injections, Intravenous; Animals; Pharmacokinetics; Drug Interactions; Half-Life